The Routledge international handbook of penal abolition - Coyle, Michael J.; Scott, David Gordon (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"The Routledge International Handbook of Penal Abolition provides an authoritative and comprehensive look at the latest developments in the 21st Century penal abolitionism movement, both reflecting on key critical thought and setting the agenda for local and global abolitionist ideas and interventions over the coming decade. Penal abolitionists question the legitimacy of criminal law, policing, courts, prisons and more broadly the idea of punishment, to argue that rather than effectively handling or solving social problems, inter-personal disputes, conflicts and harms, they actually increase individual and societal problems. The Routledge International Handbook of Penal Abolition is organized around six key themes: Social movements and abolition organizing, Critiques of resistance to the penal state, Voices from imprisoned and marginalized communities, Diversity of abolitionist thought, International perspectives on abolitionism, Building new justice practices as a response to social and individual wrongdoing. A global-centred and world-encompassing project, this book provides the reader with an alternative and critical perspective from which to reflect, and raises the visibility of abolitionist ideas and strategies in a time when there is considerable discussion of how we will move forward in response to what has given rise to the criminalizing system: white supremacy, racial capitalism, and human wrongdoing. It is essential reading for all those engaged with punishment and penology, criminology, sociology, corrections and critical prisons studies. It will appeal to any reader who seeks an innovative response to the calamitous failures of the modern criminalizing system"--
Abolition now : social movements in abolitionism -- Resisting penal subjugation -- Abolitionism is for the oppressed -- Abolitionism : decolonising, decriminalizing and decarcerating -- Abolitionist reimaginings -- Activist toolbox : abolitionist campaign tools, manifestos and statements.
OCLC-licensed vendor bibliographic record.
Keywords: Prison-industrial complex; Prisons -- Moral and ethical aspects; Imprisonment -- Moral and ethical aspects; Discrimination in criminal justice administration; SOCIAL SCIENCE / Criminology; SOCIAL SCIENCE / Penology